Development of Inventory Database System Using Radio Frequency Identification (International Journal of Engineering and Computer Science, 2013)
Inventory database system using Radio-frequency identification (RFID) is a database management system with RFID tag as a triggering input and as a security to the system. The idea is to develop a systematically database for lecturer to request stationary from office’s faculty by enhancing it with the RFID and establish a Local Area Connection (LAN) connection. The aim for this project is to enable user to have an easy access for requesting stationary from office's faculty stationary. The RFID tag that has a unique identification number will be the input/password for user/administrator to access into the system. The Microsoft SQL Server 2005 will be used as a database that stored all the information and inventory related to this system. The interface for this system will be developed using Microsoft Visual Basic 6.0 and as the interaction between the hardware and software integration. As the result, the configuration of hardware to software can be done thus enabling the user and administrator to begin using the system. As the future work, the e-mail alert reminder can be adding-up as an additional notification on approval status of the requested item in order to enhance the system.